Manufactured landscapes : [videorecording (DVD)] - Baichwal, Jennifer; Burtynsky, Edward, 1955- (Zeitgeist Films, 2007)
Follows photographer Edward Burtynsky as he travels through China photographing the effects of that country's massive industrial revolution.